Listening to Change: Understanding Student Success Through Developmental Vectors and Evidence Based Qualitative Research - Emerson, María Evelia (Evidence Based Library and Information Practice, 2026)
Objective – The objective of this study is to explore whether undergraduate students’ definitions and understanding of student success evolve over time and identify the factors and experiences that shape that development. It also examines implications for how academic libraries can better support student success. The study builds on observations from a prior study that students’ definitions evolved in distinct ways.Methods – The author used a qualitative, inductive approach to conduct semi-structured interviews with twenty undergraduates (n=20). The data was analyzed using thematic analysis and inductive coding to identify key themes related to student experiences, pivotal life moments, evolving definitions of student success, and environmental influences. Interviews from the prior study (n=30) were reanalyzed to assess consistency, yielding a combined dataset of 50 participants.Results – Inspired by Chickering’s (1969) use of vectors in his student identity development theory, the author identified six student success development vectors based on the recurring themes from interviews in both studies (n=50). These vectors illustrate how students define, understand, and experience student success in non-sequential and complex ways. They also underscore the critical role of students' identities, backgrounds, and lived experiences in shaping their evolving understandings of success.Conclusion – The research confirmed that undergraduate students' definitions and understanding of student success are not static but evolve over time, influenced by personal contexts. This study highlights the importance and insight that student voices bring to both student success librarianship and broader higher education conversations. Additionally, the findings support the idea that the concept of student success deserves more understanding in its complexity and should be viewed as individualized and context-dependent, to be defined by students themselves. For academic libraries, this research underscores the importance of holistic support that recognizes students’ perspectives and unique experiences.